Ethnoscience Studies in Traditional Food of North Maluku "Papeda" and Its Implementation of Chemical Concepts in Science Learning - Tohe, Humairah Ansar; Sriyati, Siti; Liliawati, Winny; Tohe, Ansar (Journal of Tropical Chemistry Research and Education, 2024)
Ethnoscience is a science learning approach that implements local wisdom (regional culture) using certain cultural products. Local wisdom can be in food and drink, traditional ceremonies, dances, games, and traditional languages. One of the traditional food-based local wisdom is Papeda. Papeda is a traditional food made from sago flour. The purpose of this research is to reconstruct the original science of the community into scientific science and to review the concept of chemistry in science learning in the process of making papeda. The research method used is descriptive qualitative research through interviews and literature studies. The results of this study indicate that the reconstruction of indigenous knowledge into scientific science from the local wisdom of traditional food typical of North Maluku, namely Papeda, can be used as a learning resource for students because it has relevance to various chemical concepts in science learning. Chemical concepts contained in the process of making papeda are substances and their changes, colloids, physical and chemical changes, thermochemistry, macromolecules (especially carbohydrates), and food and nutrients with their relationship to the digestive system.